Diastolic pulmonary gradient predicts outcomes in group 1 pulmonary hypertension (analysis of the NIH primary pulmonary hypertension registry). (October 2016) - Mazimba, Sula; Mejia-Lopez, Eliany; Black, George; Kennedy, Jamie L.W.; Bergin, James; Tallaj, Jose A.; Abuannadi, Mohammad; Mihalek, Andrew D.; Bilchick, Kenneth C.
Abstract: Background: Diastolic pulmonary gradient (DPG), calculated as the difference between pulmonary artery diastolic pressure and mean pulmonary capillary wedge pressure ≥ 7 mmHg is associated with pulmonary vascular disease and portends poor prognosis in heart failure (HF). The prognostic relevance of DPG in group 1 pulmonary hypertension (PH) is uncertain. Methods: Using the Pulmonary Hypertension Connection (PHC) risk equation for 225 patients in the NIH-PPH, the 5-year probability of death was calculated, which was then compared with DPG using a Cox proportional hazards model. Kaplan-Meier survival curves were determined for two cohorts using the median DPG of 30 mmHg as cutoff, and significance was tested using the log-rank test. Results: The mean age was 38.1 ± 16.0 years old, 63% female, and 72% were "white". The mean DPG was 31.6 mmHg ± 13.8 mm Hg and only 1.8% had a DPG <7 mm Hg. Increasing DPG was significantly associated with increased 5-year mortality even after adjustment for the PHC risk equation (HR 1.29 per 10 mm Hg increase). When DPG was dichotomized based on the median of 30 mm Hg, the HR for DPG >30 mm Hg with respect to 5-year mortality was 2.03. After adjustment for pulmonary artery systolic pressure (PASP), increasing DPG remained significantly associated with decreased 5 years survival (HR 1.99 for DPG > 30 mm Hg). Conclusions: DPG is independently associated with survival in group 1 PH patients even after adjustment for the PHC risk equation or PASP. Patients with increased DPG had a 2-fold increased risk of mortality. The use of DPG for guiding treatment and prognosis in group 1 PH should be further investigated. Highlights: Diastolic pulmonary gradient (DPG), the difference between pulmonary artery diastolic pressure and mean capillary wedge pressure, ≥ 7 mmHg is associated with pulmonary vascular remodelling. Group 1 Pulmonary hypertension patients have broader distribution of DPG than group 2 pulmonary hypertension category. Increasing DPG is associated with worse mortality in Group 1 pulmonary hypertension.